Perubahan Pengetahuan dan Sikap Remaja Setelah Diberi Promosi Kesehatan Mental - Rahmawati, Yeni; Widodo, Arif (Journal of Telenursing (JOTING), 2024)
The aim of this research is to determine differences in changes in knowledge and attitudes of adolescents after being given mental health promotion. This research method is pre-experimental design with one pre-test-posttest group. This research was conducted on students of SMAN 2 Sukoharjo who were given health promotion. The results of the research before being given health promotion were 91 people who had sufficient knowledge. After being given health promotion, 91 people had good knowledge. Before being given the health promotion, 93 teenagers had Sika in the low category. After being given health promotion, 91 people had attitudes in the high category. There is a difference in teenagers' knowledge before and after health promotion (p value = 0.001). There is a difference in teenagers' attitudes before and after health promotion (p value = 0.001). The conclusion is that there is an increase in knowledge and attitudes after being given health promotion regarding mental health in adolescents. It is recommended that nurses provide health promotion to teenagers directly in schools. Keywords: Adolescents, Health Promotion, Mental health